Mechanistic, in-silico and in vitro studies with nitrofurans reveal potent leishmanicidal activity and inhibition of trypanothione reductase - Andrés-Rodríguez, Julia; González-Montero, María-Cristina; García-Fernández, Nerea; Galano-Frutos, Juan-José; Rosa, Maria-Cristina de; Ferreira, Patricia; Pérez-Pertejo, María-Yolanda; Reguera, Rosa M.; Balaña-Fouce, Rafael; García-Estrada, Carlos (International journal for parasitology -- drugs and drug resistance, 2025)
Visceral leishmaniasis caused by Leishmania infantum and Leishmania donovani is one of the neglected tropical diseases (NTDs) caused by trypanosomatids with treatment options limited to outdated drugs often causing adverse effects and promoting drug resistance. Previous antileishmanial drug discovery campaigns have identified nitroheterocyclic molecules with high efficacy and a high selectivity index. Therefore, we have evaluated on our screening platform of fluorescent L. donovani amastigotes, the antileishmanial activity of seven nitrofuran derivatives: furazolidone, nitrofurazone, nitrofurantoin, nifurtimox, 5-nitro-2-furaldehyde diacetate, PYZD-4409 and 5-nitro-2-furonitrile. These compounds showed good efficacy against axenic and intramacrophage amastigotes, most of them showing low cytotoxicity in mammalian cell lines. These nitrofuran derivatives induced reactive oxygen species production in axenic amastigotes and inhibited trypanothione reductase (TryR) either in uncompetitive or competitive manner, thus suggesting that their mechanism of action involves increased oxidative stress caused by an imbalance in redox metabolism. Furazolidone exhibited the most promising antileishmanial profile, and molecular docking analysis revealed consistency with the strongest TryR uncompetitive inhibitory effect, demonstrating its high affinity for an alternative binding site near the substrate (oxidized trypanothione) pocket. Docking results also highlighted PYZD-4409 as the compound with the highest binding affinity, and showed consistency with its competitive inhibition mechanism. Furthermore, similar binding modes identified across L. donovani TryR and other homologous proteins suggest the potential broad-spectrum activity of these nitrofuran derivatives, thus underscoring their importance as promising candidates for the development of novel antileishmanial therapies with broad-spectrum applications. [Display omitted]